Strategic Defection in Bilateral Trade - Christoph Lülfesmann (University of Bonn, Bonn Graduate School of Economics (BGSE), 2001)
The paper studies a generic bilateral trade model with relationship-specific investments. Only the seller invests, and subsequent trade becomes inefficient if his investments are too low. We show that the seller may defect strategically under a fixed-price contract even though he attains any arbitrary surplus when expending the (second-best) investment. In this case, no general mechanism facilitates trade and the parties should not start their relationship. Also, the defection problem may be more severe when the parties trade after the buyer's valuation has been disclosed, as compared to a situation where the parties have to complete trade under uncertainty.
Keywords: D23; H57; L51; 330; Bilateral Trade; Hold-Up; Specific Investments; Incomplete Contracts